Seroepidemiology of Rift Valley Fever in Basrah - Rahman Kadhum Muhsen (Kufa Journal for Veterinary Medical Sciences, 2012)
This study was conducted in Basrah to evaluate the seroepidemiological prevalence of Rift valley fever in Basrah . Serum samples were collected from 1215 sheep from 5 distinct regions in Basrah and submitted to the ELISA test to estimate the titer of specific antibodies against rift valley fever virus . The result revealed that , the overall seroprevalence RVF in Basrah was 0. 89 % . There was no significant differences in the seroprevalence of RVF among different regions in Basrah (  P > 0.05 ) . The highest seroprevalence were reported in sheep older than 3 years compared with other age groups and this difference were statistically highly significant ( P < 0.01 ) . On other hands there was no statistical difference in the seroprevalence of RVF between male and female (  P > 0.05 ) .